Design of video games for children`s diet and physical activity behavior change - Baranowski, T.; Thompson, D.; Buday, R.; Shirong Lu, A.; Baranowski, J. (International Journal of Computer Science in Sport, 2010)
Serious video games (VG) offer new opportunities for promoting health related diet and physical activity change among children. Games can be designed to use storylines, characters, and behavior change procedures, including modeling (e.g., engaging characters make changes themselves, and face and overcome challenges related to fruit and vegetable (FV) and physical activity (PA) goal attainment and/or consumption), skill development (e.g., asking behaviors; virtual recipe preparation), self regulatory behaviors (problem solving, goal setting, goal review, decision making), rewards (e.g., points and positive statements generated by the program), immediate feedback (e.g., through characters and/or statements that appear on the computer screen at critical decision points), and personalization (e.g., tailored choices offered at critical junctures, based on responses to baselines questions related to preferences, outcome expectancies, etc). We are in the earliest stages of learning how to optimally design effective behavior change procedures for use in VG, and yet they have been demonstrated to change behavior. As we learn, VG offer more and better opportunities for obesity prevention that can adjust to individual needs and preferences.